Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1093/toxsci/kfp241
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Regenerative Proliferation as the Mode of Action for Diuron-Induced Urothelial Carcinogenesis in the Rat

Abstract: Diuron, a substituted urea herbicide, is carcinogenic to the urinary bladder of rats at high dietary levels. Its proposed carcinogenic mode of action (MOA) includes urothelial cytotoxicity and necrosis followed by regenerative cell proliferation and sustained urothelial hyperplasia. Cytotoxicity could be induced either by urinary solids or by chemical toxicity by diuron and/or metabolites excreted in the urine. Diuron was not genotoxic in a previous single-cell gel (comet) assay, but possible cross-linking act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 26 publications
6
23
1
4
Order By: Relevance
“…genotoxic agent, what is in line with information from this laboratory that reported nongenotoxicity of the herbicide under two different comet assay protocols (Nascimento et al, 2006;Rocha et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…genotoxic agent, what is in line with information from this laboratory that reported nongenotoxicity of the herbicide under two different comet assay protocols (Nascimento et al, 2006;Rocha et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies from this laboratory reported absence of diuron genotoxicity in the standard alkaline version of the comet assay with urothelial and peripheral blood cells (Nascimento et al, 2006). Besides, a modified version of the comet assay developed in vitro with CHO cells indicated that diuron also does not induce DNA cross-links (Rocha et al, 2009). …”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations